2022
DOI: 10.3390/curroncol29010021
|View full text |Cite
|
Sign up to set email alerts
|

Safety Related to the Timing of Radiotherapy and Immune Checkpoint Inhibitors in Patients with Advanced Non-Small Cell Lung Cancer: A Single Institutional Experience

Abstract: Background: The safety impact of radiotherapy (RT) timing relative to immune checkpoint inhibitors (ICIs) for advanced non-small-cell lung cancer (NSCLC) is unclear. We investigated if RT within 14 days (Interval 1) and 90 days (Interval 2) of ICI use is associated with toxicities compared to RT outside these intervals. Methods: Advanced NSCLC patients treated with both RT and ICIs were reviewed. Toxicities were graded as per CTCAE v4.0 and attributed to either ICIs or RT by clinicians. Associations between RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…We retrieved 2798 records from three databases, of which 709 duplicated records were excluded. After a series of filters, eventually, 25 journal articles 6 , 7 , 8 , 9 , 10 , 11 , 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 were included for the present meta‐analysis. In some articles, two or more arms of combined treatment of ICB + RT in articles were analyzed separately in our meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved 2798 records from three databases, of which 709 duplicated records were excluded. After a series of filters, eventually, 25 journal articles 6 , 7 , 8 , 9 , 10 , 11 , 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 were included for the present meta‐analysis. In some articles, two or more arms of combined treatment of ICB + RT in articles were analyzed separately in our meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies 8 , 9 , 10 have concluded that synchronous use is more beneficial to patients, and some studies 2 , 3 , 7 have shown evidence to support the use of ICB after RT. Remaining studies 11 , 12 concluded that the order of use does not affect the efficacy to patients. The controversy also focused on the application of new RT technology.…”
Section: Introductionmentioning
confidence: 99%